MULTIPLEX SYBR® GREEN-REAL TIME PCR (qPCR) ASSAY FOR THE DETECTION AND DIFFERENTIATION OF Bartonella henselae AND Bartonella clarridgeiae IN CATS - Rodrigo Staggemeier; Diogo André Pilger; Fernando Rosado Spilki; Vlademir Vicente Cantarelli (Revista do Instituto de Medicina Tropical de São Paulo, 2014)
A novel SYBR® green-real time polymerase chain reaction (qPCR) was developed to detect two Bartonella species, B. henselae and B. clarridgeiae, directly from blood samples. The test was used in blood samples obtained from cats living in animal shelters in Southern Brazil. Results were compared with those obtained by conventional PCR targeting Bartonella spp. Among the 47 samples analyzed, eight were positive using the conventional PCR and 12 were positive using qPCR. Importantly, the new qPCR detected the presence of both B. henselae and B. clarridgeiae in two samples. The results show that the qPCR described here may be a reliable tool for the screening and differentiation of two important Bartonella species.